Structural, Magnetic Properties of Nix-1ZnxFe2O4Nanocrystals by coprecipitation method. (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The compound Nix-1ZnxFe2O4 (0≤x≤1) was prepared by co-precipitation method. The structural and morphological aspects were evaluated by X-ray powder diffraction (XRD), scanning electron microscopy (SEM), infrared Spectroscopy (FTIR), The magnetic properties were evaluated using vibration Sample magnetometer (VSM). The replacement of zinc in the Nix-1ZnxFe2O4 nanocrystals increased the lattice parameter of the ferrite nanoparticles monotonically from 8.388 to 8.422 Å and decreased the size of the nanocrystals from 16.56 to 12.95 nm. FTIR spectroscopy showed that replacement with Zn up to x = 0.5 in Nix-1ZnxFe2O4 nanocrystals led to the migration of iron ions from tetrahedral to octahedral sites, which led to an improvement in the value of the saturation magnetization which reached to 47.6 emu / g. At the same time, the coercivity decreased from 45.2 Oe to 10.6 Oe due to the increment in zinc content except for the sample x = 0.5.